2011
DOI: 10.4012/dmj.2011-011
|View full text |Cite
|
Sign up to set email alerts
|

A novel composite-to-composite adhesive bond mechanism

Abstract: The purpose of this study was to determine if adhesion between various resin composites can occur by a chelation reaction of elemental ions. The surface composition of four commercially available resin composites (Beautifil II, Clearfil AP-X, Estelite Σ Quick and Solare) were measured by X-ray fluorescence analysis. Composite-to-composite adhesion with conventional silane coupling treatment was compared to self-etching primer treatment and evaluated by conventional shear bond strength testing. Our results dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Another minimal approach regarding the repair of resin composite restorations without silane coupling pretreatment has also been reported [23]. Furthermore, Akimoto et al [24] reported that silane coupling treatment is not necessary for the adhesion of resin composites, depending on the composition of the fillers, owing to the chelating reaction between the acidic monomer and the Sr and Ba alkaline-earth metal ions. AB (a self-etching primer) contains an acidic monomer, while the CRs (BeautiCore LC) contain a S-PRG filler, which itself contains strontium as a glass component.…”
Section: Discussionmentioning
confidence: 99%
“…Another minimal approach regarding the repair of resin composite restorations without silane coupling pretreatment has also been reported [23]. Furthermore, Akimoto et al [24] reported that silane coupling treatment is not necessary for the adhesion of resin composites, depending on the composition of the fillers, owing to the chelating reaction between the acidic monomer and the Sr and Ba alkaline-earth metal ions. AB (a self-etching primer) contains an acidic monomer, while the CRs (BeautiCore LC) contain a S-PRG filler, which itself contains strontium as a glass component.…”
Section: Discussionmentioning
confidence: 99%
“…Nakase et al [37] reported that S-PRG filler-containing CAD/CAM resin composite blocks demonstrated acceptable physical properties and wear performance for clinical use. Moreover, an S-PRG filler-containing CAD/CAM resin composite crown is advantageous for primary tooth restoration because it can be cemented using a conventional glass-ionomer cement through the chelation reaction between Sr and polycarboxylic acid [38].…”
Section: Restorative Treatmentmentioning
confidence: 99%
“…The FL-Bond II primer is an acetone-free adhesion promoting monomer with no incorporation of HEMA [25]. This primer contains ethanol, pure water, a phosphonic acid monomer (6-MHPA), and a carboxylic acid monomer (4-AET) [10,26]. The bonding contains 1,6bis(methacr yloxy-2-ethoxy-carbonylamino)-2,4,4trimethylhexane (UDMA), HEMA, TEGDMA and S-PRG filler (surface pre-reacted glass-ionomer) [27].…”
Section: Preparation Of the Adhesive Systemsmentioning
confidence: 99%